Balancing tradition and innovation: The impacts of AI on university students' language learning journey - En, Lam Binh; Thuan, Tran Thi Bich; Tha, Nguyen Phun Huynh; Anh, Lai Le Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
This article examines traditional language learning methods within the context of AI's growing influence. It acknowledges the challenges students face in learning new languages and explores AI tools, such as ChatGPT, highlighting both their opportunities and challenges. While the benefits of AI, such as personalized feedback, are highlighted, a deeper critique of potential drawbacks, such as oversimplification and reduced interaction, is necessary. The article calls for a balance between AI and traditional methods, suggesting that AI should complement, not replace, traditional teaching methods to strengthen the argument.